America today, 1932-1934 [and] The World in review - Film and Photo League (U.S.); Museum of Modern Art (New York, N.Y.). Circulating Film Library (New York: Museum of Modern Art Film Library, 1982)
America today features protest against the first U.S. envoy from Nazi Germany, against the jailing of striking workers in New York, and against the framing of the Scottsboro Boys. The World in review depicts world leaders (Mussolini, Hitler, FDR) preparing for war.
Photographer, editor, Leo Seltzer.
Keywords: World politics -- 1919-1932.; United States -- History -- 1919-1933.